SOSIALISASI PENERAPAN PSAK 1 DALAM PENYAJIAN PEMBUKUAN AKUNTANSI BERBASIS KOMPUTER TERHADAP UMKM JASA SALON AMY - Kusuma, Mufid Hadi; Arini, Anya Nurpuspa; Mutiyah, Mutiyah; Basuki, Veronica Cipta Simone; Umam, Ikeu Nur Ikhdal; Sulistiowati, Puji; Rahmadi, Zara Tania; Setiawan, Indra (PUAN INDONESIA, 2024)
One of the common problems faced by MSMEs is the lack of adequate maintenance of financial records on their business activities. Financial management that has not been completely separated from the family's personal finances causes the implementation of the basic accounting system in the business does not run optimally. Many MSMEs consider that business bookkeeping is too complicated and less important, especially because of the lack of skills and awareness of the sustainability of their businesses. This study aims to provide an overview of the application of basic computerized accounting systems in SMEs and understand financial statements in accordance with PSAK No. 1. In order to improve the quality of accounting records that are currently suboptimal, the implementer utilizes an empowerment method through a bottom-up approach, involving active participation from the grassroots or the community at large. With this method, MSMEs and service providers actively engage in identifying issues, seeking appropriate solutions, and collectively taking steps to resolve these problems. This ensures that the implementation of a computer-based basic accounting system in the "Salon Amy" MSME can proceed.